Development of a PRODELIC-Based Instrument for Assessing Students’ Mathematical Literacy and Disposition - Emas Marlina; Hartono; Wahyu Setyaningrum (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2026)
This study aims to develop and validate a PRODELIC-based instrument for assessing students’ mathematical literacy and mathematical disposition, ensuring that the instrument demonstrates adequate validity and is suitable for evaluating these competencies in mathematics learning. This research method uses Design-Based Research (DBR) which consists of problem analysis, design and innovation development, cyclical repetition and implementation, and reflection evaluation. The research instrument is a validity instrument consisting of a validity assessment sheet for the PRODELIC learning model components and learning support tools. The data analysis used is qualitative and quantitative. The validity of the model, lesson plans, and worksheets was evaluated based on the assessment of experts and practitioners using the Aiken validity index. The results of the study showed that the Aiken's V value for all learning model component instrument items was in the range of 0.85 to 0.95, the lesson plan instrument was in the range of 0.9 to 0.95, and the worksheet was in the range to 1. These scores means that the model is valid and suitable for developing mathematical literacy and disposition. These findings indicate that the PRODELIC model and its supporting instruments are valid and suitable for mathematics learning aimed at developing students’ mathematical literacy and disposition. Theoretically, PRODELIC contributes an integrated framework that combines Deeper Learning and Project-Based Learning, while practically, it provides teachers with a structured approach for designing mathematics instruction that promotes mathematical literacy and disposition.